Anti-dumping Duties and the Byrd Amendment - David R. Collie; Hylke Vandenbussche (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2004)
The Byrd amendment to US anti-dumping law distributes the revenue from anti-dumping duties imposed on foreign firms to the domestic firms that lodged the complaint of dumping. When the government sets its anti-dumping duty to maximise a welfare function that attaches greater weight to the profits of the domestic industry than to consumer surplus or tax revenue, it is shown that the Byrd amendment will lead to lower duties and higher welfare if the weight on the profits of the domestic industry is sufficiently large. Also, the Byrd amendment makes it less likely that the anti-dumping duty will be prohibitive.
Keywords: F12; F13; 330; Tariffs; US trade policy; WTO; Cournot oligopoly.; Antidumping; Außenhandelspolitik; WTO-Regeln; Oligopol; USA